Analysis of deviant behaviors and family functions in the population at risk of internet addiction among primary and secondary school students in Chengdu city, Sichuan province of China - Xiujuan Zhang; Xiujuan Zhang; Xi Huang; Xi Huang; Qiong Chen; Qiong Chen; Yan Song; Yan Song; Xixi Jiang; Junxia Zhou; Junxia Zhou; Xiufang Zhao; et al. (Frontiers in Public Health)
BackgroundThis study explores the correlation between internet addiction (IA) and deviant behaviors among primary and secondary school students. It analyzes the impact of family functional factors, such as family relationships, parent–child communication, and parental control, on IA. The findings aim to provide a scientific basis for educators and parents to develop targeted preventive and intervention measures.MethodsA cross-sectional survey was conducted using self-administered questionnaires among 8,816 students from five primary and secondary schools in Chengdu. The questionnaire included basic information about students and their families, Young’s Internet Addiction Scale, Shek’s Deviant Behavior Scale, and the Chinese Family Assessment Instrument (C-FAI). Chi-square tests and t-tests were used to compare differences between the at-risk group for internet addiction and the normal population. Statistically significant variables were extracted and included in the hierarchical regression model, with the level of significance set at α = 0.05.ResultsThe detection rate of IA risk among primary and secondary school students was 14.11%, and the detection rate of deviant behaviors in this group was 85.21%. Deviant behaviors such as deceit (r = 0.201), running away from home (r = 0.215), and damaging others’ property (r = 0.209) showed a weak correlation with the risk of internet addiction, and the differences were statistically significant (p < 0.05). The results of the hierarchical regression analysis showed that all five dimensions of family environment and delinquency scores positively predicted internet addiction. Specifically, the change in R2 was 8.7% for mutual concern among family members and 9.7% for student delinquency behavior. Together, family environment and delinquency behavior explained 22.1% of the variance.ConclusionPrimary and secondary school students at risk of IA are more likely to exhibit deviant behaviors, which show a weak correlation with IA. Gender and grade level significantly impact the risk of IA, indicating that male students and those in higher grades require more attention. Strengthening family interventions, especially in areas of mutual communication, family conflict resolution, and parental control, can help prevent IA among primary and secondary school students.